Unraveling the impact of purification and alloying elements on corrosion performance and passivation of magnesium alloys - Arash Fattah-alhosseini; Razieh Chaharmahali; Alireza Askari; Sajad Alizad; Mosab Kaseem (Journal of Magnesium and Alloys)
The passivation of magnesium (Mg)-based alloys is an electrochemical behavior. The formation of a protective surface film results in passivation. The composition of this surface layer is influenced by the substrate alloy, which in turn affects the passive behavior. Recent studies have examined the composition of the surface film when Mg alloys undergo corrosion. Most of these studies have focused on the presence of Mg hydroxide (Mg(OH)2) and MgO in the layer. However, a systematic examination of the impact of alloying elements on the stability of the passive layer is lacking. The essential question for developing a corrosion-resistant Mg-based alloy with passive protection is: which are the best and most efficient elements that can form a passive layer when alloyed with Mg? Passivity in a Mg alloy could be achieved by using a non-equilibrium technique to supersaturate the matrix phase with a high concentration of a strong passivating element. This review paper examines and explores the potential of creating a passive Mg-based alloy using metallurgical methods, like alloying and purification. Additionally, this paper explains key concepts about the passivity of Mg alloys and proposes possible methods to create a passive Mg alloy.